The Letters of Arthur Schnitzler to Hermann Bahr Edited, annotated, and with an Introduction - Daviau, Donald G. (UNC Studies in the Germanic Languages and Literatures, 1978)
Arthur Schnitzler (1862-1931) and Hermann Bahr (1863-1934), two of the leading literary personalities in turn-of-the-century Vienna, maintained a friendship that lasted forty years. These letters contribute to an understanding of the life, times, and writings of both of these important authors and provide another perspective on the Jung-Wien group. This edition also includes Daviau's valuable annotations to the text, as well as brief biographies of figures mentioned in the letters. The introduction includes useful summaries of related texts not available for publication at the time.